Fish bone waste as catalyst for biodiesel production - Sulaiman, Sarina; N. Khairudin, Syakirah; Jamal, Parveen; Alam, Md Zahangir (Universiti Malaysia Kelantan, 2015)
In this study, fish bone waste was used as a new catalyst for biodiesel production. Therefore, instead of throwing away the fish bone waste, it will be utilized as a source for catalyst that can provide significant benefit to the environment. Fish bone also can be alternative source of calcium oxide instead of using eggshell, crab shell, snail shell and others. The calcinations of catalyst were optimized using Response Surface Methodology (RSM) using Central Composite Design by two factors; temperature and time. Under optimal furnace condition of calcinations for 2 at 900°C, reaction time 4 hours, reaction temperature 65°C and reaction speed 300 rpm, the optimal FAME conversion was at highest of 90%.